2022
DOI: 10.1002/jbm4.10580
|View full text |Cite
|
Sign up to set email alerts
|

Rare Diseases That Impersonate One Another:X‐LinkedHypophosphatemia andTumor‐InducedOsteomalacia, a Retrospective Analysis of Discriminating Features

Abstract: Tumor‐induced osteomalacia (TIO) is a rare paraneoplastic disease characterized by frequent fractures, bone pain, muscle weakness, and affected gait. The rarity of TIO and similar presentation to other phosphate‐wasting disorders contribute to a high misdiagnosis rate and long time to correct diagnosis. TIO is curable by tumor resection, so accurate diagnosis has significant impact on patients' emotional and economic burden. Current diagnostics for TIO rely on decades‐old literature with poor phenotypic valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The potential for the biochemical differentiation of TIO with XLH continues to be investigated. One retrospective analysis indicated that patients with TIO had significantly higher levels of FGF23 and alkaline phosphate, significantly lower levels of phosphorus and 1,25(OH) 2 D, but similar levels of 25-hydroxyvitamin D (25[OH]D) compared with patients with XLH [36]. A potential role for sclerostin in the differentiation of TIO and XLH has also been proposed, with one cross-sectional study reporting decreased levels in patients with TIO and increased levels in patients with XLH [49].…”
Section: Evaluation Of Patients With Suspected Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for the biochemical differentiation of TIO with XLH continues to be investigated. One retrospective analysis indicated that patients with TIO had significantly higher levels of FGF23 and alkaline phosphate, significantly lower levels of phosphorus and 1,25(OH) 2 D, but similar levels of 25-hydroxyvitamin D (25[OH]D) compared with patients with XLH [36]. A potential role for sclerostin in the differentiation of TIO and XLH has also been proposed, with one cross-sectional study reporting decreased levels in patients with TIO and increased levels in patients with XLH [49].…”
Section: Evaluation Of Patients With Suspected Tiomentioning
confidence: 99%
“…A careful medical history should include the age of onset and accompanying symptoms, which may include bone pain, muscle weakness and pain, fatigue, decreased exercise tolerance, gait disturbance, height loss, increased thoracic kyphosis, pectus carinatum, and fractures [ 30 , 33 , 34 , 35 , 36 , 37 ]. Cases have been reported in individuals as young as 9 months old [ 38 ], with a median age of onset of 46 years and a range of 9 months–90 years [ 7 , 39 ].…”
Section: Recognizing Clinical Signs and Symptoms That Raise Suspicion...mentioning
confidence: 99%